(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2015)
For more than 30 years there was a judge that traced the line for everyone, attempting to transform in discipline, in scientific construction, the knowledges acquired through an extraordinary investigative commitment. On his birth, this “Rivista” considers necessary to underline the intellectual debt towards Giovanni Falcone that the academic community in the organized crime field has.